Genetic and biological diversity of the Pea seed-borne mosaic virus isolates occurring in Czech Republic - Safárová, D; Navrátil, M; Petrusová, J; Pokorný, R; Piáková, Z (Acta virologica, 2008)
Eight isolates of the Pea seed-borne mosaic virus (PSbMV) from the Czech Republic were studied regarding their biological and molecular characteristics. Molecular characterization using RT-PCR was done on the 5'(Nter)NIb-CP-UTR3' region amplified using universal CPUP/P9502 primer pair and the newly designed PSB8812/PSB944, and PSB8800/PSB9440 primer pairs, respectively. Sequential and phylogenetic analysis of CP-UTR3' region from all isolates showed that the available Czech and GenBank PSbMV isolates were distributed into 4 clusters in agreement with their diversification and according to their biological characteristics (i.e. pathotype). The molecular data were confirmed by biological testing on different pea cultivars. The Czech isolates were distributed into two pathotypes, the P-1 (7 isolates) and P-4 (1 isolate).
Keywords: Molecular Sequence Data; sekvence aminokyselin; Sequence Alignment; hrách setý; Česká republika; Potyvirus; genetická variace; Czech Republic; Pisum sativum; Genetic Variation; Viral Proteins; Amino Acid Sequence; fylogeneze; nemoci rostlin; molekulární sekvence - údaje; virové proteiny; Phylogeny; sekvenční seřazení; Plant Diseases